2021
DOI: 10.3390/su13084220
|View full text |Cite
|
Sign up to set email alerts
|

The County-Scale Economic Spatial Pattern and Influencing Factors of Seven Urban Agglomerations in the Yellow River Basin—A Study Based on the Integrated Nighttime Light Data

Abstract: The integrated night light (NTL) datasets were used to represent the economic development level, and visual analysis was carried out on the evolution characteristics of the economic spatial pattern of various urban agglomerations in the Yellow River Basin (YRB), at a county-scale, in 1992, 2005, and 2018. The Global Moran’s I and the local Getis-Ord G methods were used to explore the overall spatial correlation and local cold–hot spot of economic development levels, respectively. The spatial heterogeneity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…As an example, Wang, J. et al examined how the economic spatial distribution of the towns and cities in the Yellow River Basin changed over time. When the precise elements influencing the level of city economic growth were analyzed using a multi-scale spatially weighted regression model, it was demonstrated that the economic, geographical pattern of urban-rural integration and development would be in the shape of a "pyramid" [26]. Spagnoli, L. et al claimed that the current social urbanization process cannot be accommodated by the old agricultural model and suggested that multifunctional agriculture plays a crucial role in the advancement of urban-rural integration.…”
Section: Review Of Research On New Urbanization and Integrated Urban-...mentioning
confidence: 99%
“…As an example, Wang, J. et al examined how the economic spatial distribution of the towns and cities in the Yellow River Basin changed over time. When the precise elements influencing the level of city economic growth were analyzed using a multi-scale spatially weighted regression model, it was demonstrated that the economic, geographical pattern of urban-rural integration and development would be in the shape of a "pyramid" [26]. Spagnoli, L. et al claimed that the current social urbanization process cannot be accommodated by the old agricultural model and suggested that multifunctional agriculture plays a crucial role in the advancement of urban-rural integration.…”
Section: Review Of Research On New Urbanization and Integrated Urban-...mentioning
confidence: 99%
“…However, the development basis, development path and strategic positioning of each urban agglomeration in the YRB are different, and the results of carbon emission reduction in recent years are also different. To promote low-carbon transformation and high-quality development in the YRB, it is necessary not only to clarify the overall carbon emission conditions but also to conduct heterogeneity analysis from the perspective of urban agglomeration differences and coordinated development [ 28 , 29 ]. At present, there are few studies on distribution dynamics, differential changes and mechanisms of carbon emission reduction from the perspective of urban agglomerations in the YRB, and there is still a lack of empirical analysis on how to better promote the process of carbon emission reduction in urban agglomerations in the YRB.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of the ecological structure of urbanization will in turn lead to an uncoordinated rate of economic development, which will result in lagging development. There are many advanced technologies available for surveying the distribution and exploitation of natural resources in the Yellow River Basin, which can help workers to obtain timely information data and take political measures [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%